Ecological Crisis in Theological Anthropology. The Necessary Recovery of the «Primordial Triangle» - Castelao, Pedro (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2020)
The current ecological crisis has in its background an anthropological crisis. The root of this anthropological crisis lies in the imbalance that, since modernity, has occurred within the «primordial triangle»: human being, God, world. The loss of the divine vertex produced the emergence of a «segment» whose polarity «self-world» has produced many tensions that have led us to the ecological crisis we are suffering today. Theological Anthropology, with the help of the categories like «interrelation», «interdependence» and «inhabitation», must contribute to a new approach to the problem by reimagining what kind of human being we are called to be and what relationship with nature we should have.
Keywords: ecological crisis; theological anthropology; Laudato si’; Anselm of Canterbury; Descartes; Kant; Harari; theology of creation